THE EFFECT OF EXERCISE AND KINESTHETIC METHODS TO BACKHAND GROUNDSTROKE SKILLS ON FIELD TENNIS GAMES - James Tangkudung; Firmansyah Dlis; M. Sahib Saleh (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2017)
This experimental research aims to know the influence of exercise and kinesthetic skills against the backhand groundstroke tennis sports field. The research was carried out at the tennis FIK UNM. Factorial design experiments using the method 2x3. The sample consists of 60 students. Technique of data analysis is a two-way analysis of variance (ANOVA) and tukey test T-: results of this research show that: (1) Wrist curl practice methods better influence from horizontal swing exercises against backhand groundstroke tennis field tennis, (2) Wrist curl practice method is better than cable rotation exercises on backhand groundstroke tennis skills, (3) Horizontal swing practice method is better than cable rotation practice on backhand groundstroke tennis skills, (4) There is interaction between wrist curl practice method, horizontal swing practice method, high rotation kinesthetic training method for backhand groundstroke tennis field tennis, (5) Wrist curl practice method is better than horizontal swing practice method against backhand groundstroke skill high tennis kinesthetic tennis, (6) wrist curl exercise method is not better his influence from the method of horizontal swing exercises against the skills of backhand groundstroke tennis kinesthetic high, (7) Cable rotation training method is better than the horizontal swing practice method against backhand groundstroke skills of high kinesthetic tennis field tennis, (8) The horizontal swing practice method is better than the wrist curl practice method for backhand groundstroke skills of low kinesthetic tennis court, (9) The cable rotation training method is better than the wrist curl practice method of backhand groundstroke skills of low kinesthetic tennis court, (10) The horizontal swing practice method is better than the cable rotation training method of backhand groundstroke skills on low kinesthetic tennis court. Keywords : Training methods, kinesthetic and backhand groundstroke skills on the tennis court